17.9k views
18 votes
Pls answer with steps

Pls answer with steps-example-1
User Billcyz
by
4.2k points

1 Answer

8 votes

Answer:

1.) (x - 13)(x - 8)

2.) x(x - 11)(x + 13)

3.) (x - 2)(x - 4)(2x + 1)

4.) (3x + 2)(3x - 1)

5.) (x - 4)(3x + 13)

Explanation:

1.) (x² - 13x - 9x + 117) + (x - 13)

2.) x(x² + x - 132) + x(x - 11)

= x(x + 12)(x - 11) + x(x - 11)

= x(x - 11)(x + 13)

3.) (2x³ - 12x² + 16x) + (x -2)(x -4)

= 2x(x² - 6x + 8) + (x -2)(x - 4)

= 2x(x² - 4x - 2x + 8) + (x -2)(x -4)

4.) 9x² - 4 + (3x + 2)

= (3x)² -2² + (3x + 2)

= (3x + 2)(3x - 2) + (3x + 2)

5.) (3x² - 48) + (x - 4)

= 3(x - 4)(x + 4) + (x - 4)

User Philip McQuitty
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.